The Coastal Platform Morphodynamics Characteristics Belang Bay, North Sulawesi Province - Christian Kumaat, Joyce; Tonly Boy Kandoli, Sontje; Tenly Moningkey, Agnes (Indonesian Journal of Geospatial, 2014)
Abstract. Coastal dynamics represent change from time to time, could be the form of coastal Â presenting effect ofsedimentation and earn also in the form of coastal backing effect of erosion.This research of coastalmorphodynamics on Belang Bay, will study by some aspect that is: beach morphology, grain size sediment andhydrodynamics activity. The purpose of this study is to see how far the influence of the morphodynamics of thecoastal damage and sensitivity (susceptibility) coastal sea water due to the influence of hydrodynamics. Methodof data collection and analysis, two main parameters were measured wave energy and beach characteristics.Knowledge on the morphodynamic behaviour of beaches was obtained from a topographic measurementsof 15 beach transects normal to the coastline. Widely used morphodynamic parameters, like the SurfSimilarity and the Surf Scaling parameters, were applied to the data, resulting in a general morphodynamiccharacterization of beaches, represented in a map of beach type distribution. In molompar beach identified bysediment material vary between finesand up to coarse sand which is distribution in each coastal circulationcell of Molompar beach.Keywords: hydrodynamics, morphodynamic, surf, similarity, coastal